2020
DOI: 10.1001/jamaoto.2019.3760
|View full text |Cite
|
Sign up to set email alerts
|

Audiology Practices in the Preoperative Evaluation and Management of Adult Cochlear Implant Candidates

Abstract: IMPORTANCE Currently, no clear guidelines exist regarding clinical testing methods for identifying adult cochlear implant (CI) candidates. Indications provided by the US Food and Drug Administration, Medicare, and private insurers are ambiguous concerning test materials and the level and mode of test presentation. This could lead to wide variability in clinical assessment and, potentially, unequal access to CIs for individuals with clinically significant hearing loss. OBJECTIVE To examine the preoperative test… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
43
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(44 citation statements)
references
References 24 publications
0
43
0
1
Order By: Relevance
“…Despite the substantial influence on CI candidacy qualification, speech perception testing in noise is not standardized across the United States, and practice variability includes extremes of the range from no testing in noise to +5 dB signal-to-noise ratio utilized to qualify patients for CIs. 37 50 It follows that patients with residual hearing who undergo CI evaluation without noise are less likely to qualify for CI compared with those who complete testing in noise. 51 To compound the obstacles associated with CI candidacy testing, patient interviews have suggested that the testing battery does not represent real-world hearing difficulties and may have an impact on whether individuals decide to proceed with surgery.…”
Section: The Cochlear Implant Processmentioning
confidence: 99%
“…Despite the substantial influence on CI candidacy qualification, speech perception testing in noise is not standardized across the United States, and practice variability includes extremes of the range from no testing in noise to +5 dB signal-to-noise ratio utilized to qualify patients for CIs. 37 50 It follows that patients with residual hearing who undergo CI evaluation without noise are less likely to qualify for CI compared with those who complete testing in noise. 51 To compound the obstacles associated with CI candidacy testing, patient interviews have suggested that the testing battery does not represent real-world hearing difficulties and may have an impact on whether individuals decide to proceed with surgery.…”
Section: The Cochlear Implant Processmentioning
confidence: 99%
“…Clinical guidelines also provide recommendations for a standardized use of the tests [10]. However, a recent survey revealed that the recommended procedures are not always followed in the clinic [33], which can lead to biased results and further complicate their interpretation.…”
Section: Introductionmentioning
confidence: 99%
“…The variability in CI rehabilitation results is considerable [1,3,37], and the concept of CI user reference data is complicated, as it is inevitable that the average performance of a large CI patient population may be an unrealistic goal for some CI users and an underachievement for others. Nevertheless, the need for CI user reference data that is collected from a large, unselected patient population under standardized, well-defined testing conditions is recognized in multiple recent publications [12,33,38].…”
Section: Introductionmentioning
confidence: 99%
“…This protocol change is supported by the report of Prentiss et al, 27 who recently noted that 100% of clinics surveyed indicated they include word tests in their pre-and postoperative test batteries, even though not all indications base candidacy on such a score. Additionally, 89% of respondents use some form of sentence testing in noise to determine CI candidacy.…”
Section: Clinical Decision-makingmentioning
confidence: 90%